Accuracy of post‐radiotherapy biopsy before salvage radical prostatectomy. (13th March 2013) - Meeks, Joshua J.; Walker, Marc; Bernstein, Melanie; Kent, Matthew; Eastham, James A.
<x xml:space="preserve">Abstract</x> Objective To determine whether post‐radiotherapy (RT) biopsy (PRB) adequately predicts the presence, location, and histological features of cancer in the salvage radical prostatectomy (SRP) specimen. Before salvage treatment, a PRB is required to confirm the presence of locally recurrent or persistent cancer and to determine the extent and location of the prostate cancer. Patients and Methods SRP was performed between 1998 and 2011 on 198 patients. All patients underwent a PRB. PRB and SRP specimens were evaluated by a genitourinary pathologist. Patients had external‐beam RT alone (EBRT; 71%) or brachytherapy with or without EBRT (29%). Results Of the men undergoing SRP, 26 (14%) were clinical stage ≥T3, with 13% of PRBs with Gleason score ≥8. Cancer was unilateral in 120 (61%) biopsies, with contralateral or bilateral prostate cancer at SRP in 49%. In the SRP specimen, cancer was multifocal in 57%. Cancer was upgraded at SRP in 58% of men, with 20% having an increase in primary Gleason grade. The accuracy of PRB varied by region from 62% to 76%, with undetected cancers ranging from 12% to 26% and most likely to occur at the mid‐gland. Conclusions Radiation‐recurrent prostate cancers were often multifocal, and biopsy missed up to 20% of tumours. More than half of the cancers were upgraded at SRP, and many that were unilateral on PRB were bilateral at SRP.